THE EMERGING ROLE(S) OF LAW IN REPRODUCTIVE HEALTH CARE IN NIGERIA: A COMPARATIVE ANALYSIS - Patrick Chukwunonso Aloamaka; Favour AdaezeIbekwe (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
There is no gainsaying the fact that the ICPD Call for Action Programme and the Beijing Conference has had pivotal roles in the evolution and growth of Reproductive Health Laws.  These reproductive health laws in turn have served as a means of resolution to Reproductive health issues which include but are not limited to issues such as early and under-aged marriage, adolescent pregnancy, harmful traditional practices examples of which include Female Genital Mutilation (FGM), widowhood practice, domestic violence, abortion, HIV/AIDS, Maternal mortality/morbidities and improper family planning. Many challenges remain in the effort to address these health issues. The major setback has been the failure of state parties (countries) to incorporate these International Reproductive Health Care instruments into their legal system as well as the implementation of these laws. This paper highlights the legality of the ICPD in the context of International Law and also focuses on the emerging roles of laws in Reproductive Health Care in Nigeria